Evaluation of a Dust-Related Power Loss Sensor for Solar Farm Management - Barnaby Portelli; Ryan D’Amato; Ivan Grech; Joseph Micallef (Energies)
As the adoption of solar photovoltaic systems continues to increase, the efficiency and reliability of these systems under real-world conditions become paramount. This paper presents a comprehensive study on the influence of dust deposition on PV panel performance, based on an innovative dust-related power loss sensor. A dust coefficient is defined, which gives the percentage loss in energy generation due to dust accumulation. This coefficient, obtained from the dust-related power loss sensor, was validated in this study in two ways: correlation with weather events monitored using data derived from a custom-built weather station and correlation with the outputs from an eight-panel reference system. Pairs of PV panels in this eight-panel system were subjected to four distinct cleaning schedules, and the energy generation from each pair was monitored. The results showed that the data from the dust-related power loss sensor system presented here are a reliable indicator of energy losses due to dust accumulation. The dust coefficient can thus be used as a real-time parameter that enables the creation of informed cost-effective cleaning schedules for large PV farms.